Sustainable Architecture for Rural Communities: The Tanzanian Family House Model - Kiranjeet Kaur Jassal; Ajay Kumar (International Journal of Rural and Regional Development, 2026)
Sustainable rural housing in East Africa must respond simultaneously to climatic stress, water scarcity, sanitation challenges, and socio-cultural practices. This article presents the Tanzanian Family House as a climate-responsive and resource-efficient housing model developed specifically for rural Tanzanian communities. The project integrates low embodied energy materials, passive environmental strategies, and decentralized infrastructure systems to create a durable and culturally grounded dwelling that can be constructed using local skills and materials. The architectural design combines rammed earth walls for thermal mass, bamboo and timber screens for ventilation and daylight control, and a floating roof system that promotes passive cooling by enhancing air movement and reducing direct solar heat gain. Water security is addressed through an impluvium-based rainwater harvesting system connected to an underground cistern, reducing dependence on external water sources. Sanitation is resolved through composting toilets and a planted evapotranspiration system for greywater treatment, enabling a closed-loop ecological cycle without chemical or mechanical inputs. The study evaluates the house using four key criteria: environmental performance, material sustainability, passive comfort strategies, and socio-cultural integration. Environmental simulations and design analysis demonstrate a reduction of indoor temperatures by 3–5°C compared to conventional rural housing, improved daylight quality, and effective cross-ventilation. The integrated water and sanitation systems significantly reduce freshwater consumption and eliminate risks of groundwater contamination. The article concludes that the Tanzanian Family House represents a scalable and adaptable prototype for sustainable rural housing in East Africa and similar tropical climates. By combining indigenous building knowledge with contemporary ecological design principles, the model offers a practical pathway toward low-carbon, resilient, and socially inclusive rural development.
Keywords: Composting toilets; Passive cooling; rainwater harvesting; rammed earth; rural architecture; sustainable housing